Constraining the thermally pulsing asymptotic giant branch phase with resolved stellar populations in the Small Magellanic Cloud. Issue 4 (18th March 2019) - Pastorelli, Giada; Marigo, Paola; Girardi, Léo; Chen, Yang; Rubele, Stefano; Trabucchi, Michele; Aringer, Bernhard; Bladh, Sara; Bressan, Alessandro; Montalbán, Josefina; Boyer, Martha L; Dalcanton, Julianne J; et al.
Abstract: The thermally pulsing asymptotic giant branch (TP-AGB) experienced by low- and intermediate-mass stars is one of the most uncertain phases of stellar evolution and the models need to be calibrated with the aid of observations. To this purpose, we couple high-quality observations of resolved stars in the Small Magellanic Cloud (SMC) with detailed stellar population synthesis simulations computed with thetrilegal code. The strength of our approach relies on the detailed spatially resolved star formation history of the SMC, derived from the deep near-infrared photometry of the VISTA survey of the Magellanic Clouds, as well as on the capability to quickly and accurately explore a wide variety of parameters and effects with thecolibri code for the TP-AGB evolution. Adopting a well-characterized set of observations – star counts and luminosity functions – we set up a calibration cycle along which we iteratively change a few key parameters of the TP-AGB models until we eventually reach a good fit to the observations. Our work leads to identify two best-fitting models that mainly differ in the efficiencies of the third dredge-up and mass-loss in TP-AGB stars with initial masses larger than about 3 M⊙ . On the basis of these calibrated models, we provide a full characterization of the TP-AGB stellar population in the SMC in terms of stellar parameters (initial masses, C/O ratios, carbon excess, mass-loss rates). Extensive tables of isochrones including these improved models are publicly available.